Experimental and numerical analysis of a serial connection of two SOFC stacks in a micro-CHP system fed by biogas. (2nd February 2017) - Kupecki, Jakub; Skrzypkiewicz, Marek; Wierzbicki, Michal; Stepien, Michal
Abstract: This paper presents the results of an evaluation of a conceptual micro-CHP unit with two serially connected integrated stack modules (ISM), each made up of two 30 SOFC cells packages. In-series connection of two identical commercial 60-cell stacks with electrolyte-supported SOFC was under evaluation. In order to achieve high overall fuel utilization in the system which enables achieving high electrical efficiency, the concept was analyzed with respect to the operational regimes typical for a commercial SOFC stack. Numerical analysis included simulation of the complete system, including fuel processor, SOFC stacks and BoP components. Additionally, an experimental setup with a commercial 1300 W SOFC stack was used to reproduce operating conditions obtained from the model. Validation of the concept was necessary to qualitatively and quantitatively determine the possibility of operating a second stack on a lean fuel originating from the anodic compartments of the first stack. Results of the analysis presented in the paper were used to aid in defining the optimal outline of a micro-CHP power system, constructed at the Institute of Power Engineering (IEN). Predictions of the models were in agreement with preliminary experiments, proving that the concept of the in-series stacks configuration is viable. Electrical efficiency increases for the system with two in-series stacks, and value of 46%LHV can be achieved in the micro-CHP system with SOFC under conservative assumptions. Highlights: Serial connection of two SOFC stacks was evaluated. Experimental and numerical study was performed. The validated model was used to predict the system performance. Model is based only on physical, geometrical and material properties of the stack. Serial connection offers several benefits, including system efficiency improvement.